Endodontic inflammatory disease: A risk indicator for a first myocardial infarction. (11th October 2021) - Sebring, Dan; Buhlin, Kåre; Norhammar, Anna; Rydén, Lars; Jonasson, Peter; ,; Lund, Henrik; Kvist, Thomas
Abstract: Aim: To study the association between endodontic inflammatory disease and a first myocardial infarction (MI). Methodology: The study comprised 805 patients with recent experience of a first MI, each gender, age and geographically matched with a control. Panoramic radiographs were available for 797 patients and 796 controls. Endodontic inflammatory disease was assessed radiographically. The sum of decayed, missing and filled teeth (DMFT) was calculated, and the number of root filled teeth and teeth with periapical lesions were recorded. The associated risk of a first MI was expressed as odds ratios (OR) with 95% confidence intervals (CI), unadjusted and adjusted for confounders (family history of cardiovascular disease, smoking habits, marital status, education and diabetes). Results: Patients who had suffered a first MI had higher DMFT (mean 22.5 vs. 21.9, p = .013) and more missing teeth (mean 7.5 vs. 6.3; p < .0001) than the healthy controls. The number of missing teeth was associated with an increased risk of a first MI (adjusted OR 1.04; CI 1.02–1.06). Conversely, decay‐free, filled teeth were associated with decreased risk (adjusted OR 0.98; CI 0.96–1.00). Analysis based on age disclosed the following variables to be associated with an increased risk of a first MI: number of decayed teeth (adjusted OR 1.18; CI 1.02–1.37, in patients <60 years), any primary periapical lesion (adjusted OR 1.57; CI 1.08–2.29, in patients <65 years) and the proportion of root filled teeth (adjusted OR 1.18; CI 1.03–1.36, in patients ≥65 years). Conclusions: More missing teeth was independently associated with an increased risk of a first MI. In addition, endodontic inflammatory disease may contribute as an independent risk factor to cardiovascular disease since untreated caries, periapical lesions and root fillings, depending on age, were significantly associated with a first MI.